Tooth Loss And Mobility In Aggressive Periodontitis Patients: A Retrospective Study - Fazid, Nurul Farahin binti; So ‘odi, Siti Mahirah binti; Yaacob, Munirah; Husain, Juzaily; Ali, Suhaila Muhammad (IIUM Medical Journal Malaysia, 2018)
Introduction: Tooth loss has much negative implication in aesthetics and oral function of an individual. Aggressive periodontitis has been known to result in rapid tissue and bone destruction and if left untreated eventually tooth loss. Hence, this study was conducted to assess the prevalence of tooth loss and tooth mobility in a group of aggressive periodontitis patients. Materials and Methods: This was a retrospective data of aggressive periodontitis patients attending IIUM Dental Clinic that has been diagnosed in year 2014 up to June 2017. The data was extracted from patients’ case records systematically using data extraction forms representing all specific objectives. IBM SPSS-24 was used for data analysis. Results: The prevalence of aggressive periodontitis patients attending IIUM dental clinic within 4 years was 4.2%. Out of this 45.5% presented with tooth loss. Most of them had being diagnosed as generalized aggressive periodontitis and showed to have high mean plaque and bleeding score compared to aggressive periodontitis with no tooth loss. However it was statistically insignificant difference (p<0.05). The tooth loss group also presented with more remaining teeth with mobility. Conclusion: Tooth loss was prevalence in aggressive periodontitis patients. Moreover, remaining teeth were also affected by some degree of mobility, which may affect the normal oral cavity functions and aesthetic. Further study with bigger sample size should be conducted to analyze the impact of the high tooth loss to the patients’ oral and general well-being.